Delivery of TRAIL-expressing plasmid DNA to cancer cells in vitro and in vivo using aminoglycoside-derived polymers. Issue 44 (21st October 2019) - Goklany, Sheba; Lu, Ping; Godeshala, Sudhakar; Hall, Andrea; Garrett-Mayer, Elizabeth; Voelkel-Johnson, Christina; Rege, Kaushal
Abstract : Novel aminoglycoside-derived polymers for therapeutic gene delivery of the TRAIL-expressing plasmid to cancer cells in vitro and in vivo . Abstract : Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a death ligand that can preferentially induce apoptosis in cancer cells over normal cells. The transmembrane form of TRAIL has been shown to elicit much stronger activity than its soluble counterpart but delivery is a potential challenge. Here, we investigated the potential of aminoglycoside-derived polymers to enhance delivery of a plasmid (pEF-TRAIL) that expresses the transmembrane form of TRAIL in order to determine the effect on cell death in vitro and tumor growth in vivo . Transgene delivery efficacy and toxicity of aminoglycoside-derived polymers was first evaluated using a GFP-expressing plasmid (pEF-GFP) at different plasmid amounts and plasmid : polymer ratios in UMUC3 bladder cancer and HeLa cervical cancer cells. Delivery of the TRAIL plasmid using aminoglycoside-derived polymers resulted in up to 60% cell death in UMUC3 and HeLa cells; TRAIL protein expression was confirmed using Western blots. TRAIL plasmid delivery resulted in a decrease in cellular procaspase-8 and an increase in TRAIL receptor DR5 levels, suggesting a role for the death receptor and caspase cascade in TRAIL-mediated apoptosis. The TRAIL plasmid did not cause cell death in normal human or mouse fibroblasts. The in vivo delivery of the TRAIL plasmid using a paromomycin-derived polymer resulted in significant reduction in tumor burden and increased survival in tumor-bearing live mice.